2013
DOI: 10.1007/s00405-013-2460-x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of lasersurgery and radiotherapy as treatment modalities in early stage laryngeal carcinoma: tumour outcome and quality of voice

Abstract: For treatment of early stage (Tis-T2) laryngeal cancer the main choice is between microlaryngoscopy with carbon dioxide laser resection (laser surgery) and radiotherapy. Because both treatments provide excellent tumour control, secondary outcome variables such, as quality of voice may be of importance in treatment preference. In this study tumour outcomes and quality of voice were analysed for a cohort of patients with early stage (Tis-T2) laryngeal (glottic) carcinoma. The "physical subscale" of the voice han… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
61
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(65 citation statements)
references
References 43 publications
4
61
0
Order By: Relevance
“…Several other studies found the same correlation between the extent of the cordectomy (types V and VI) and a worse subjective vocal outcome. 3,16,17 For exclusively T1a lesions treated with TLM, Czecior and colleagues 18 found that 54% of patients had a G score of 0 to 1, 78% an R score of 0 to 1, 96% a B score of 0 to 1, 99% an A score of 0 to 1, and 58% an S score of 0 to 1. Compared with preoperative voice, Aaltonen and colleagues 14 found a significant improvement in average self-reported hoarseness on a visual analog scale of 0 to 100 after 6 months (50/100 vs 59/100 preoperatively), improving further after 12 months (43/100).…”
Section: How Is Voice Subjectively After Transoral Laser Microsurgery?mentioning
confidence: 98%
“…Several other studies found the same correlation between the extent of the cordectomy (types V and VI) and a worse subjective vocal outcome. 3,16,17 For exclusively T1a lesions treated with TLM, Czecior and colleagues 18 found that 54% of patients had a G score of 0 to 1, 78% an R score of 0 to 1, 96% a B score of 0 to 1, 99% an A score of 0 to 1, and 58% an S score of 0 to 1. Compared with preoperative voice, Aaltonen and colleagues 14 found a significant improvement in average self-reported hoarseness on a visual analog scale of 0 to 100 after 6 months (50/100 vs 59/100 preoperatively), improving further after 12 months (43/100).…”
Section: How Is Voice Subjectively After Transoral Laser Microsurgery?mentioning
confidence: 98%
“…With arguably comparable, excellent disease-specific outcomes reported for each treatment modality, 7,8 consideration of the postoperative voice plays a significant role when deciding which treatment is the most advantageous. 8 However, there is still considerable debate regarding expected voice outcomes, [9][10][11][12] with widely varying opinion among health care providers on which modality offers the best voice outcome.…”
Section: Introductionmentioning
confidence: 99%
“…8 However, there is still considerable debate regarding expected voice outcomes, [9][10][11][12] with widely varying opinion among health care providers on which modality offers the best voice outcome. 10 Despite the postoperative voice playing a significant role in treatment decision making, there is no consistent voice profile after TLM.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To date the majority of research on voice outcomes following early glottic cancer (Tis-T2) has explored the impact of either radiotherapy or transoral laser microsurgery on voice quality and functional outcomes [4][5][6]. Findings from this body of research suggests that both methods of organ-preservation treatment impact vocal quality and function to a similar extent, with the majority of patients expected to present with persistent, predominantly mildmoderate changes to voice quality [7][8][9].…”
Section: Introductionmentioning
confidence: 99%